Stochastic parameter regression models - Newbold, Paul.; Bos, Theodore (Beverly Hills ; London : SAGE, 1985)
This introduction to stochastic parameter regression models is more advanced and technically difficult than other papers in this series. These models allow relationships to vary through time, without forcing the analyst to specify and analyze the causes of the time-varying relationships.
"A SAGE university paper."
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Regression analysis; Stochastic analysis